2017
DOI: 10.1007/s10803-017-3235-9
|View full text |Cite
|
Sign up to set email alerts
|

How to Implement Robots in Interventions for Children with Autism? A Co-creation Study Involving People with Autism, Parents and Professionals

Abstract: The aim of this study was to gain insight into how robots can be practically implemented into current education and therapy interventions for children with autism spectrum disorder (ASD). This qualitative study included focus groups and co-creation sessions. 73 Participants (professionals and adults with ASD) took part in 13 focus groups to elicit requirements for robot assisted interventions. Additionally, 22 participants (professionals, parents of children with ASD and adults with ASD) generated ideas for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(118 citation statements)
references
References 20 publications
5
95
0
2
Order By: Relevance
“…Although the survey was only limited to 74 participants (37 from Italy and 37 from United Kingdom), overall participants in this study showed a global positive attitude towards Socially Assistive Robotics (SAR) paradigms. Apart from that, some researchers also conducted studies investigating the establishment of robot-based therapeutic protocol for CWA training [21][22][23] and the needs of therapists towards having a robotic platform in helping CWA [24,25].…”
Section: Novelty Of Our Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the survey was only limited to 74 participants (37 from Italy and 37 from United Kingdom), overall participants in this study showed a global positive attitude towards Socially Assistive Robotics (SAR) paradigms. Apart from that, some researchers also conducted studies investigating the establishment of robot-based therapeutic protocol for CWA training [21][22][23] and the needs of therapists towards having a robotic platform in helping CWA [24,25].…”
Section: Novelty Of Our Reviewmentioning
confidence: 99%
“…In our review, many researchers intended to provide a robotic intervention program for children aged below 15 as shown in Table I. There are some researchers who also performed their research for individuals with autism until the age of 20 [86] while some researchers conducted experiments with future therapists and professionals on the robot-therapy protocol and training implementation [23,24]. This is also important in establishing a standardized protocol or standard operating procedure for robotics platform in autism intervention programs [21,51,[101][102][103][104].…”
Section: Demographics Of Participantsmentioning
confidence: 99%
“…Many of the robots found in the literature are still in a prototype stage and not commercially available. It is highly recommended that knowledge from ASD practice reaches technical robot developers to guide robot development so that studies can be conducted with robot interventions that are carefully designed to meet the specific needs of this target group and that utilise the potential power of robots [20].…”
Section: Resultsmentioning
confidence: 99%
“…It was unclear, however, whether these educators considered, overall, robots to be relevant, appropriate, and feasible for their SEND settings and learners-and, most relevant to the current study, whether they might be especially useful for autistic learners. Huijnen et al (2017) took a related approach, combining focus groups, and co-creation sessions with autism stakeholders and professionals (including teachers and other school-based roles, all in the Netherlands) to develop 10 specific "intervention templates" for the humanoid robot, KASPAR. These included clear statements of goals, and explicitly mapped out the planned roles and "flow" of an interaction between a child, robot, and professional.…”
Section: Introductionmentioning
confidence: 99%